An Innovative Olive Pâté with Nutraceutical Properties - Pierpaolo Cavallo; Irene Dini; Immacolata Sepe; Gennaro Galasso; Francesca Luisa Fedele; Andrea Sicari; Sergio Bolletti Censi; Anna Gaspari; Alberto Ritieni; Matteo Lorito; Francesco Vinale (MDPI AG, 2020)
Food plays a central role in health, especially through consumption of plant-derived foods. Functional foods, supplements, and nutraceuticals are increasingly entering the market to respond to consumer demand for healthy products. They are foods, supplements, and ingredients which offer health benefits beyond the standard nutritional value. Some benefits are associated with phenolic compounds and phytochemicals with antioxidant properties. An olive pâté (OP) was added with antioxidants derived from olive mill wastewater (OMWW) to obtain a functional product rich in phenolic compounds. The olive pâté is produced from the ground olive pericarp, which shows an excellent natural antioxidant content. The OMWW is a waste product from oil processing, which is also rich in phenolic compounds. The result was a product rich in trans-resveratrol, OH tyrosol, and tyrosol in concentrations such as satisfying the European community's claims regarding the possible antioxidant action on plasma lipids with excellent shelf-life stability. The total phenolic content was assayed by a colorimetric method, the antioxidant activity by the ABTS [(2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)] test, the phenolic profile by Q Exactive Orbitrap LC-MS/MS. The shelf-life stability was confirmed by yeast, molds, and total microbial count, pH, and water activity determinations, and the best pasteurization parameters were determined. The palatability was judged as excellent.